2021
DOI: 10.3389/fagro.2021.720215
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Genetic Mapping of PM1, a Powdery Mildew Resistance Gene in Cannabis sativa L.

Abstract: Powdery mildew is among the most common diseases of both hemp- and marijuana-type cultivated Cannabis sativa. Despite its prevalence, no documented studies have characterized sources of natural genetic resistance in this pathosystem. Here we provide evidence for the first resistance (R) gene in C. sativa, represented by a single dominant locus that confers complete resistance to an isolate of the powdery mildew pathogen Golovinomyces ambrosiae, found in the Pacific Northwest of the United States. Linkage mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The utility of disease-tolerant genotypes that may have been developed through selective breeding and genotype screening is an important aspect of IDM for stock plants. Diseasetolerant genotypes of cannabis have been identified for a number of pathogens, including root rot (Fusarium oxysporum) [23], powdery mildew (Golovinomyces ambrosiae) [10][11][12]32], leaf blight (Neofusicoccum parvum) [33], and bud rot (B. cinerea) [34,35] (Figure 8). Recent research suggests that specific defense genes may play a role in certain host-pathogen interactions, leading to a resistant phenotype [11][12][13]36].…”
Section: Utilizing Disease-tolerant Genotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…The utility of disease-tolerant genotypes that may have been developed through selective breeding and genotype screening is an important aspect of IDM for stock plants. Diseasetolerant genotypes of cannabis have been identified for a number of pathogens, including root rot (Fusarium oxysporum) [23], powdery mildew (Golovinomyces ambrosiae) [10][11][12]32], leaf blight (Neofusicoccum parvum) [33], and bud rot (B. cinerea) [34,35] (Figure 8). Recent research suggests that specific defense genes may play a role in certain host-pathogen interactions, leading to a resistant phenotype [11][12][13]36].…”
Section: Utilizing Disease-tolerant Genotypesmentioning
confidence: 99%
“…Diseasetolerant genotypes of cannabis have been identified for a number of pathogens, including root rot (Fusarium oxysporum) [23], powdery mildew (Golovinomyces ambrosiae) [10][11][12]32], leaf blight (Neofusicoccum parvum) [33], and bud rot (B. cinerea) [34,35] (Figure 8). Recent research suggests that specific defense genes may play a role in certain host-pathogen interactions, leading to a resistant phenotype [11][12][13]36]. The impact of cannabis genotype on disease development at the flowering stage will be discussed later in this review.…”
Section: Utilizing Disease-tolerant Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting resistance (R) and susceptibility (S) genes are one way to increase a plant's resistance. A recent study has identified a powdery mildew resistance (R) gene in a Cannabis sativa cultivar, designated PM1, that confers resistance to the pathogen Golovinomyces ambrosiae (Mihalyov and Garfinkel, 2021). Improving food quality of seed and seed oil is also possible.…”
Section: Targets For Hemp Crop Improvementmentioning
confidence: 99%
“…Since a similar situation has been observed between hop (Humulus lupulus, the closest relative of cannabis) and Podosphaera macularis (Henning et al, 2011), it is likely that such gene-for-gene interactions exist between cannabis and PM. Indeed, the first gene conferring complete resistance to an isolate of PM has recently been identified in cannabis (Mihalyov and Garfinkel, 2021). In grapevine, resistance is usually considered polygenic, and there appears to be a diverse range of responses to invasion by Erysiphe necator, from penetration resistance to the induction of plant cell death (Feechan et al, 2011).…”
Section: Genetic Variation Within Clade V Csmlos: a Quest Toward Durable Resistancementioning
confidence: 99%